DUTCH AUCTION - Mávila H., Daniel (2002)
The auctions are system which let us determine the prize of the product or the service of the demands who are express their maximum payment. These auctions approach the perfect market. In the present work gives details about the mechanism of collocation of the dutch auction utilize now national and international.